2018
DOI: 10.1002/smll.201703691
|View full text |Cite|
|
Sign up to set email alerts
|

Palladium‐Decorated Silicon Nanomesh Fabricated by Nanosphere Lithography for High Performance, Room Temperature Hydrogen Sensing

Abstract: A hydrogen (H ) gas sensor based on a silicon (Si) nanomesh structure decorated with palladium (Pd) nanoparticles is fabricated via polystyrene nanosphere lithography and top-down fabrication processes. The gas sensor shows dramatically improved H gas sensitivity compared with an Si thin film sensor without nanopatterns. Furthermore, a buffered oxide etchant treatment of the Si nanomesh structure results in an additional performance improvement. The final sensor device shows fast H response and high selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 49 publications
(79 reference statements)
1
55
0
Order By: Relevance
“…In the case of dry air, t 90 was increased by a factor of 2 (t 90 = 50 s against 20 s in Ar). Whilst in humid air, the response time was much slower with t 90 = 250 s. Similar results which show different response times as a function of the carrying gas and of the presence of humidity have been obtained previously [68,71,72]. Yet, the detection time t detect in this latter case is still lower than 1s as shown in the insert of fig 8.b.…”
Section: Selectivity ; H 2 In Dry or Humid Airsupporting
confidence: 84%
“…In the case of dry air, t 90 was increased by a factor of 2 (t 90 = 50 s against 20 s in Ar). Whilst in humid air, the response time was much slower with t 90 = 250 s. Similar results which show different response times as a function of the carrying gas and of the presence of humidity have been obtained previously [68,71,72]. Yet, the detection time t detect in this latter case is still lower than 1s as shown in the insert of fig 8.b.…”
Section: Selectivity ; H 2 In Dry or Humid Airsupporting
confidence: 84%
“…Chemically sensitive inorganic elements, which have high affinity with odorless target gases, can supplement these missing detection capabilities. Palladium (Pd) has been widely used as a functional material for hydrogen (H 2 ) sensing, which is undetectable with a biological sensory system, because H 2 is colorless and odorless. Recent chemical sensitive transistors demonstration included such gas detectors (Figure i), where Pd was used as the primary perception element in the FET‐based transducer to induce current change in response to H 2 absorption .…”
Section: Olfactory and Gustatory Sensory System‐inspired Electronicsmentioning
confidence: 99%
“…However, the weakness of those materials was that the heat source is needed in their MEMS platform. To solve the MEMS gas sensing at room temperature, metal particles were reported for gas sensing with an advantage in good selectivity than metal oxide [82,83]. Gao et al developed silicon-based nanosphere lithography for hydrogen (H 2 ) sensing as shown in Figure 5b.…”
Section: Mems Gas Sensormentioning
confidence: 99%